Government environmental governance, fiscal decentralization, and carbon intensity of the construction industry - Yuhao Sun; Minghui Liu; Yong Lv (Scientific Reports)
Abstract In recent years, China’s economic development is dominated by an eco-friendly and low-carbon transition, making the low-carbon advancement of the construction sector urgent. Local governments play a crucial role in this process. This paper, utilizing provincial panel data from 2007 to 2021, empirically analyzes the impact of government environmental governance (EG) on the carbon intensity of the construction industry (CCEI) through the panel regression, spatial econometric and dynamic threshold models. The findings indicate that (1) EG has a significant inverted U-shaped effect on CCEI, with initial increases in carbon intensity followed by reductions once EG intensity surpasses a certain level. (2) Significant spatial spillover effects reveal that increased EG in one region exerts a similar inverted U-shaped impact on both local and neighboring CCEI. (3) Under China’s fiscal decentralization framework, two dimensions—vertical decentralization and horizontal competition—serve as forms of fiscal decentralization, each with dynamic threshold effects: EG’s influence on CCEI turns negative under high vertical decentralization, and positive under intense horizontal competition. These results could offer insights from China’s emission reduction experiences in the energy-intensive sector, serving as a valuable reference for environmental decision-makers worldwide.